Cost analysis of telerehabilitation after arthroscopic subacromial decompression. - Pastora-Bernal, José Manuel; Martín-Valero, Rocío; Barón-López, Francisco Javier (Sage Publications, 2017)
Results The estimated total cost analysis shows a preliminary cost differential in favour of the telerehabilitation group, meaning that for each participant's total intervention, telerehabilitation saves 29.8% of the costs. Real cost analysis, only for received treatments, shows a cost differential in favour of telerehabilitation, meaning that for each participant's total intervention, telerehabilitation saves 22.15% of the costs incurred for conventional rehabilitation. Conclusions Our study provides direct and meaningful information about telerehabilitation opportunities and can be an essential component in further cost evaluations for different strategies after surgical procedures. This study demonstrates that there was a trend towards lower healthcare costs after ASD. Managers now have the responsibility to decide whether to implement telerehabilitation based on clinical and economic data.
Keywords: Hombros - Enfermedades; Rehabilitación - Innovaciones tecnológicas; Fisioterapia; Servicios de salud - Análisis coste-beneficio; Telerehabilitation; Cost analysis; Physiotherapy; Rehabilitation budget; Shoulder impingement syndrome